Construction of a syntrophic Pseudomonas putida consortium with reciprocal substrate processing - Burýšková, Barbora; Miró-Bueno, Jesús; Popelářová, Barbora; Gavendová, Barbora; Goñi-Moreno, Ángel; Dvořák, Pavel (Synthetic biology (Oxford, England), 2025)
Synthetic microbial consortia can leverage their expanded enzymatic reach to tackle biotechnological challenges too complex for single strains, such as biosynthesis of complex secondary metabolites or waste plant biomass degradation and valorisation. The benefit of metabolic cooperation comes with a catch-installing stable interactions between consortium members. Here, we established a mutualistic relationship in the synthetic consortium of Pseudomonas putida strains through reciprocal processing of two disaccharides-cellobiose and xylobiose-obtainable from lignocellulosic residues. Two strains were engineered to hydrolyse and metabolize these sugars: one grows on xylose and hydrolyses cellobiose to produce glucose, while the other grows on glucose and cleaves xylobiose to produce xylose. This specialization allows each strain to provide essential growth substrate to its partner, establishing a mutualistic interaction, which can be termed reciprocal substrate processing. Key enzymes from Escherichia coli (xylose isomerase pathway) and Thermobifida fusca (glycoside hydrolases) were introduced into P. putida to broaden its carbohydrate utilization capabilities and arranged in a way to instal the strain cross-dependency. A mathematical model of the consortium assisted in predicting the effects of substrate composition, strain ratios, and protein expression levels on population dynamics. Our results demonstrate that modulating extrinsic factors such as substrate concentration can help in balancing fitness disparities between the strains, but achieving this by altering intrinsic factors such as glycoside hydrolase expression levels is much more challenging. This study presents reciprocal substrate processing as a strategy for establishing an obligate dependency between strains in the engineered consortium and offers valuable insights into overcoming the challenges of fostering synthetic microbial cooperation.
Keywords: Pseudomonas putida; disaccharides; mathematical model; reciprocal substrate processing; synthetic consortium